Penyelenggaraan Jenazah pada Masyarakat Muslim: Tinjauan Mazhab Fikih terhadap Praktik Keagamaan Lokal di Kabupaten Takalar - Laman, Ilham; Lewa, Irfan (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2026)
The organization of the body in Islam is a collective obligation (fardhu kifayah) which is not only ritual, but also functions as the social glue of the ummah. In practice, the organization of funerals in the Indonesian Muslim community often interacts with local customs, thus creating a dynamic between sharia guidance and tradition. This study aims to analyze the practice of organizing bodies in Kalabbirang Village, Pattallassang District, Takalar Regency, and examine the role of fiqh assistance in harmonizing traditional practices with the provisions of Islamic law. This study uses a descriptive qualitative approach with an interpretive paradigm and participatory action research (PAR) method. Data was collected through participant observations, in-depth interviews with casscows, religious leaders, and the community, and documentation of funeral practices. Data analysis was carried out by comparing field findings against the provisions of the four main madhhab of fiqh, namely Shafi'i, Hanafi, Maliki, and Hanbali. The results of the study show that around 80% of the practice of organizing the body in Kalabbirang Village has been in accordance with the fiqh of Shafi'i as the dominant madzhab, while the main deviation is found in the symbolic elements of custom, especially in the body of the elder. A comparative analysis of the four madhhabs shows that some local practices are still within the spectrum of tolerable fiqh, especially in the perspective of the Hanafi and Maliki madhhabs. Fiqh assistance based on comparative dialogue has proven to be effective in increasing public understanding, reducing practices without a basis in sharia, and encouraging transformation from customary-based practices to more normative practices without eliminating socio-cultural functions. This study concludes that educational, participatory, and contextual religious assistance is able to strengthen the practice of arranging a legitimate body according to fiqh while maintaining social harmony. These findings contribute to the development of socio-fiqh studies at the village level and offer a model of mentoring that can be replicated in Muslim communities with similar cultural characteristics.